Synthesis and characterization of carbon monoxide-releasing molecules (CORMS) as bioactive agents / Lee Shiaw Xian - Lee , Shiaw Xian (2021)
Despite the toxicity of CO, the development of carbon monoxide-releasing molecules (CORMs) has gained increasing popularity since the discovery of the potential therapeutic properties of CO towards human body. In this study, four series of UV activable photoCORMs with the general structure of ML(CO)4 and M2L(CO)8 (Bimetallic), where M = Cr, Mo, and W, were synthesized by reacting group 6 hexacarbonyl (Cr, Mo, and W) with four new Schiff base ligands based on phenanthroline containing fluorene, 2-hydroxynaphthalene, 2-hydroxy-3-methoxy and phenylene-phenanthroline as side groups (Correspond to L1, L2, L3, and L4). All the synthesized photoCORMs release CO in the presence of UV light (365 nm). All compounds were characterized by FT-IR, 1H-NMR, 13C-NMR, and CHN elemental analysis. Twelve X-ray crystal structures were obtained out of the sixteen synthesized compounds. The half-life and the number of CO released of the synthesized photoCORMs were studied using a three-layered myoglobin solution which is a modified version of the standard myoglobin assay. Chromium photoCORMs C1, C2, C3, and C4 had much shorter half-life compared to molybdenum and tungsten photoCORMs. Molybdenum and tungsten photoCORMs were stable in 10% DMSO-PBS solution in the absence of light over 48 hours but chromium photoCORMs showed signs of decomposition. All compounds were subjected to anticancer and antimicrobial studies in the absence and presence of UV light illumination. The synthesized photoCORMs showed notable photo-induced cytotoxicity against human colorectal cancer cell lines (HT-29 and HCT 116) and showed remarkedly high selectivity when tested against the human normal colon fibroblast (CCD18-Co). However, all photoCORMs were generally non-active against all the tested microbes and only the second and the third series photoCORMs displayed slight photo-induced antimicrobial activities. The SwissADME simulation predicted that most of the synthesized compounds possess “drug-like” properties.